Pengaruh Faktor Biotik dan Abiotik Terhadap Pertumbuhan Terong Bulat (Solanum melongena L.) - Warsito, Kabul (JURNAL AGROPLASMA, 2023)
Eggplant (Solanum melongena L) is a type of vegetable plant belonging to the Solanaceae family. Eggplant plants produce fruit that is liked and in demand by many people. The area of eggplant cultivation is still small and the form of cultivation culture is still second ary and not yet intensive. This research was conducted to determine thein fluence of biotic and abiotic factors on egg plant growth and productivity. Observation of round eggplant was carried out by recording the growth parameters of round egg plant including plant height, number of leaves, stem diameter, number of branches, number of flowers, number of fruits, fruit diameter, and fruit fresh weight. The abiotic environmental parameters observed included temperature, soil pH, rain fall, and weather conditions. For biotic factors include pests, diseases, and weeds. The results of the observed growth parameter data above show that plant height, stem diameter, number of leaves, number of branches, number of flowers, number of fruits, fruit diameter, and fruit fresh weight experience dan increase in growth although not significantly. The most common type of pestis the snail with an averag eof 5.5. The most common types of disease per week were at the age of 7 weeks after planting with an average of 4.67. The results of observing the abiotic data above include temperature, Â pH, rain intensity and light intensity, showing an average temperature of 26 â°C for soil pH of 6, rain intensity of 19.44% and light intensity of 80.56%. Observations on the growth of round eggplant show data results that continue to increase a midst environmental conditions, both weather and ecosystem, which wereless supportive.Â Keywords: abiotic, biotic, eggplant